Modeling and Tracking Control of Micropipette Oocyte Enucleation Based on Fractional Calculus - Zhang, Yujie; Li, Bingxin; Liu, Yaowei; Zhao, Xin (IEEE transactions on industrial electronics (1982), 2025)
The protocol of somatic cell nuclear transfer technology requires oocyte enucleation with a micropipette. This operation is destructive and critical to the further development of reconstructed oocytes. As an aspiration control problem, the viscoelastic property of extracted material, complicated dynamics, great uncertainty, and disturbance bring about difficulties on the subject. To address this issue, this article models the enucleation process with fractional-order calculus. With the same number of parameters, it is shown that the fractional-order models have better fitting performance than integer-order models. In addition, more terms and more parameters can be added to fractional-order models, which strengthens the modeling ability. Based on the identified incommensurate fractional-order model, an adaptive sliding mode controller is proposed to deal with the unknown system parameters and disturbance. In the numerical simulation, the fractional-order controller gets a small overshoot ( < 5% ) and no oscillation, while the integer-order controller gets a large overshoot ( > 25% ) and fast oscillation. Experiments on the micromanipulation system compare the fractional-order, integer-order and traditional PID controllers. The results show that the proposed fractional-order controller has shorter arrival time, less arrival velocity, less root mean square error (RMSE), higher success rate and higher cleavage rate. The higher cleavage rate of the proposed fractional-order controller means lower damage to oocytes, which is meaningful for the completion of somatic cell nuclear transfer.